Expert Perspectives on Acne, Melasma, Polymorphic Light Eruption, and Role of Sunscreens: A Nationwide Survey - Manjula Suresh; Krishna Manjunath (International Journal of Clinical Dermatology, 2026)
Objective: To assess clinical practice patterns, treatment preferences, safety monitoring practices, and clinicians' perceptions of a botanical extract-based sunscreen formulation containing multiple plant-derived extracts, octinoxate, and titanium dioxide in the management of acne, melasma, and polymorphic light eruption (PLE) among dermatologists in India. Methods: A cross-sectional, nationwide, questionnaire-based survey was conducted among practicing dermatologists across India using a structured 22-item questionnaire. The survey evaluated clinical practice patterns in the management of acne, melasma, and PLE, including treatment preferences, photoprotection strategies, safety monitoring practices, and clinicians' perceptions of the extract-based sunscreen formulation containing multiple plant-derived extracts, octinoxate, and titanium dioxide. Data were analyzed using descriptive statistics. Results: A total of 623 dermatologists participated in the survey. Oily skin was reported by 46% of respondents as the most common presenting complaint among patients with acne, while 50% indicated that acne was more frequently encountered in female patients. Clindamycin (45.75%) and benzoyl peroxide (44.30%) were the most commonly preferred first-line treatments for teenage acne. The majority (70.95%) reported occasionally encountering topical antibiotic resistance in acne vulgaris during routine practice. Malar melasma (48.64%) was identified as the most frequently encountered clinical subtype, and melasma was considered the most common cause of facial pigmentation by 67% of respondents. Approximately 64% of dermatologists reported regularly monitoring patients for treatment-related adverse effects and medication-associated complications. Based on the 5-point Global Improvement Scale, around 46% of respondents observed marked improvement in sun-induced hyperpigmentation, ultraviolet protection, PLE, and solar urticaria with the extract-based sunscreen formulation. Conclusion: This nationwide survey highlights clinical practice patterns in the management of acne, melasma, and PLE among Indian dermatologists. The extract-based sunscreen formulation is perceived to provide clinical benefits in photoprotection and the management of sun-induced dermatoses, supporting its use as an adjunctive sunscreen in routine dermatological practice.